2010
DOI: 10.1038/onc.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

A novel interaction between HER2/neu and cyclin E in breast cancer

Abstract: HER2/neu (HER2) and cyclin E are important prognostic indicators in breast cancer. Since both are involved in cell cycle regulation we investigated whether there was a direct interaction between the two. HER2 and cyclin E expression levels were determined in 395 breast cancer patients. Patients with HER2-overexpression and high levels of cyclin E had decreased 5-year disease-specific survival compared with low levels of cyclin E (14% versus 89%, P < .0001) In vitro studies were performed in which HER2-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 32 publications
3
42
0
1
Order By: Relevance
“…HE-12 antibody, which is commonly used to detect cyclin E by Western blot analysis, revealed that, although EL was expressed in all cell lines, LMW-E was expressed only in three of the tumor cell lines (SKBR3, AU565, and MDA-MB-436) as previously reported. 54,55 The only other antibody that showed similar pattern of full-length and LMW-E expression was the C-19 antibody (Figure 1). We next interrogated which one of the eight antibodies could differentially detect full-length (nuclear) and LMW-E (cytoplasmic) by immunostaining.…”
Section: Identification Of Anti-cyclin E Antibodies That Differentiatmentioning
confidence: 99%
“…HE-12 antibody, which is commonly used to detect cyclin E by Western blot analysis, revealed that, although EL was expressed in all cell lines, LMW-E was expressed only in three of the tumor cell lines (SKBR3, AU565, and MDA-MB-436) as previously reported. 54,55 The only other antibody that showed similar pattern of full-length and LMW-E expression was the C-19 antibody (Figure 1). We next interrogated which one of the eight antibodies could differentially detect full-length (nuclear) and LMW-E (cytoplasmic) by immunostaining.…”
Section: Identification Of Anti-cyclin E Antibodies That Differentiatmentioning
confidence: 99%
“…In particular, shortening of the G1 phase promotes S phase entry in the cell cycle (12). Cyclin E and Skp2 are key factors controlling G1/S phase transition, and the overexpression of cyclin E and Skp2 induces cell proliferation (13). In the present study, we initially investigated the association of cyclin E and Skp2 levels with cell proliferation in the A549 and H446 lung cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin E expression and, consequently, cyclin E/CDK2 activity is closely associated with the G1/S checkpoint (12). Various studies have indicated that cyclin E is overexpressed in several tumor cells, such as breast cancer cells, and it has been reported to be a prognostic biomarker (13,14). p27…”
Section: Introductionmentioning
confidence: 99%
“…4). Cyclin E expression has been shown to be regulated by HER2 expression status, in that HER2 knockdown resulted in reduced cyclin E level and reduced cyclin E-associated kinase activity (Mittendorf, 2010). In addition, HER2-overexpressing breast cancers that also show increased cyclin E expression have lower 5 year disease-free survival versus those that have lower cyclin E levels (Mittendorf, 2010).…”
Section: Role Of P27 and Cdk2 In Her2-overexpressing Breast Cancermentioning
confidence: 99%
“…Cyclin E expression has been shown to be regulated by HER2 expression status, in that HER2 knockdown resulted in reduced cyclin E level and reduced cyclin E-associated kinase activity (Mittendorf, 2010). In addition, HER2-overexpressing breast cancers that also show increased cyclin E expression have lower 5 year disease-free survival versus those that have lower cyclin E levels (Mittendorf, 2010). Recently, cyclin E overexpression 12 in HER2-overexpressing breast cancer cells that have acquired trastuzumab resistance was shown to be due to amplification of the cyclin E gene (Scaltriti, 2011).…”
Section: Role Of P27 and Cdk2 In Her2-overexpressing Breast Cancermentioning
confidence: 99%